Analysis Of Students' Critical Thinking Skills With The Learning Cycle 5e Learning Model On Stoichiometry Material - Yenni Kurniawati (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This research aimed at analyzing and knowing the difference on critical thinking ability of the tenth-grade students of Science between before and after implementing Learning Cycle 5E learning model. It was conducted on the second semester in the Academic Year of 2017/2018 at the tenth grade of Science 2 of Islamic Senior High School of Darul Hikmah Pekanbaru, and the material was about Stoichiometry. This research was Descriptive, and the one group pretest-posttest design was used. Purposive sampling was used in this research and 21 students were the samples. The instrument was essay in the forms of pretest and posttest, and the instruments used to strengthen the data were observation sheet and interview. The data analysis result showed that student critical thinking ability taught by using Learning Cycle 5E learning model was on good category. The most dominant indicator of high, medium, and low student critical thinking ability was giving simple explanation with N-Gain that was 0.63, and the lowest indicator was making further explanation with N-Gain that was 0.39. The result of student interview showed that students were interested in Learning Cycle 5E learning.